2022
DOI: 10.3390/polym14132559
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization of Graphene—Hexagonal Boron Nitride-Based Kevlar–Carbon Hybrid Fabric Nanocomposites

Abstract: Polymer nanocomposites have been gaining attention in recent years. The addition of a low content of nanomaterials into the matrix improves mechanical, wear, thermal, electrical, and flame-retardant properties. The present work aimed to investigate the effect of graphene and hexagonal boron nitride nanoparticles on Kevlar and hybrid fiber-reinforced composites (FRP). Composites are fabricated with different filler concentrations of 0, 0.1, 0.3, and 0.5 wt.% by using a hand layup process. Characterizations like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…For graphite, the diffraction peak at 2θ = 26.3 corresponds to the (002) reflection, 36 and it shifts to 17.7 after hydrothermal treatment and modification with flame retardant, indicating that the spacing and dispersibility of graphene increased after hydrothermal treatment. 37 Figure . 1c, d show the 31 P and 1 H NMR spectra of phosphorus/nitrogen-containing silane compound D, respectively. The attribution of these peaks is as follows: 1 H NMR (DMSO-d 6 , 400 MHz): δ = 0.33 ppm (q, 2H, Si CH 2 CH 2 ), 1.1 ppm (q, 2H, CH 3 CH 2 O Si ), 1.22 ppm (q, 2H, CH 3 CH 2 CH 2 -), 2.49 ppm (q, 2H, CH 2 CH 2 NH ), 3.52 ppm (q, 2H, CH 3 CH 2 O Si ), 7-8 ppm (m, Ar H).…”
Section: Characterization Of D-grmentioning
confidence: 99%
See 3 more Smart Citations
“…For graphite, the diffraction peak at 2θ = 26.3 corresponds to the (002) reflection, 36 and it shifts to 17.7 after hydrothermal treatment and modification with flame retardant, indicating that the spacing and dispersibility of graphene increased after hydrothermal treatment. 37 Figure . 1c, d show the 31 P and 1 H NMR spectra of phosphorus/nitrogen-containing silane compound D, respectively. The attribution of these peaks is as follows: 1 H NMR (DMSO-d 6 , 400 MHz): δ = 0.33 ppm (q, 2H, Si CH 2 CH 2 ), 1.1 ppm (q, 2H, CH 3 CH 2 O Si ), 1.22 ppm (q, 2H, CH 3 CH 2 CH 2 -), 2.49 ppm (q, 2H, CH 2 CH 2 NH ), 3.52 ppm (q, 2H, CH 3 CH 2 O Si ), 7-8 ppm (m, Ar H).…”
Section: Characterization Of D-grmentioning
confidence: 99%
“…The attribution of these peaks is as follows: 1 H NMR (DMSO-d 6 , 400 MHz): δ = 0.33 ppm (q, 2H, Si CH 2 CH 2 ), 1.1 ppm (q, 2H, CH 3 CH 2 O Si ), 1.22 ppm (q, 2H, CH 3 CH 2 CH 2 -), 2.49 ppm (q, 2H, CH 2 CH 2 NH ), 3.52 ppm (q, 2H, CH 3 CH 2 O Si ), 7-8 ppm (m, Ar H). 31 P NMR (DMSO-d 6 , 400 MHz): δ = 32.7 ppm. The phosphorus in D induces two individual peaks at 32.7 and 14.5 ppm, respectively, while the DOPO peak appears at 13-17 ppm, indicating that the phosphorus/nitrogen-containing silane compound was successfully synthesized.…”
Section: Characterization Of D-grmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some research showed that the application of lime-treated soil caused tensile failure and serious deformation problems in some projects [ 10 , 11 , 12 ]. Hence, a great deal of materials were used by researchers to improve the limitations of lime-treated soil, and found that fibers and fly ash were better modification materials [ 13 , 14 , 15 , 16 , 17 ]. For example, some studies showed that fibers had a good effect on the tensile strength, ductility, crack resistance, and brittle failure of lime-treated soils to some extent, while that of fly ash could enhance its shear strength, bearing capacity, and deformation resistance [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%